Interdisciplinary work in advising urban social movements - Santos, Francine Helfreich; de Oliveira, Ana Cristina Oliveira; Bienenstein, Regina (Cuadernos de Trabajo Social, 2024)
This article is the product of reflections based on activities within the scope of an action program at the Federal Fluminense University (Brazil) entitled “Public universities and the right to the city: advising social movements in the State of Rio de Janeiro”. The article discusses the experience of technical consultancy as an interdisciplinary university activity linked to social movements, where dialogue with social movements is used to enhance their protagonism, organizational capacity and autonomy in the struggle for social rights that are currently denied by government, in particular the right to the city and housing. The article examines as a case study the advice provided to the Fight for Housing Forum, a space that brings together residents and leaders of the city of Niterói (in Rio de Janeiro). It is organized into two parts, in addition to the introduction and conclusions. The first part presents a brief contextualization of urban and housing planning and the popular movement in Niteroi, and the second discusses the practices, obstacles and challenges encountered in this process of advising the Fight for Housing Forum, noting the role of free, secular, high-quality and socially engaged public universities.
Keywords: Social Movements; University Extension; Technical assistance; Social service; Right to Housing